KINERJA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARANGANYAR DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN - Riskha Amallia Indriawati (Master of Public Administration, Universitas Slamet Riyadi, 2019)
the performance of Population and Civil Registration Agency ofKaranganyar needs continuously carried out and improved to realizebetter implementation of population administration.The research purposewas described performance Population and Civil Registration Agency ofKaranganyar Regency in population administration services.Performanceis a multidimensional construct, the measurement also varies dependingon the complexity of the factors that build up the performance. Theperformance assessment indicator was used performance assessmentindicator from Agus Dwiyanto (2006: 50-51) consist of productivity,service quality, responsiveness, responsibility, and accountability.This isqualitative descriptive research.The research was carried out inPopulation and Civil Registration Agancy of Karanganyar.The data wereused primary and secondary data.Data collection techniques were usedinterviews, observation, and documentation.The research informants areheads of fields and staff of the Population and Civil Registration Agencyof Karanaganyar and the people who use products/services.Data analysistechnique was used Miles and Huberman’s active model. The validitydata testing was used triangulation techniques.Based on the researchresults, it can be concluded that 1) the productivity of the issuance ofpopulation documents reaches 87%;2) The Population and CivilRegistration Agency of Karanganyar Regency has provided threecounters to serve the issuance of population administrations;3)Responsiveness in the issuance of population documents was evidencedby the responsive in receiving input and complaints from the public;4)Responsibility in the population administration services was indicated bythe fulfillment of regulations on the issuance of populationadministration;and 5) Accountability in population administration wasindicated periodic accountability report to the administrative publicofficials.Key words: productivity, service quality, responsiveness, responsibility,accountability